IAENG Transactions on Engineering Technologies Special Edition of the World Congress on Engineering and Computer Science 2011 - Kim, Haeng Kon.; Ao, Sio-Iong.; Rieger, Burghard B.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2013)
This volume contains thirty revised and extended research articles written by prominent researchers participating in an international conference in engineering technologies and physical science and applications. The conference serves as good platforms for the engineering community to meet with each other and to exchange ideas. The conference has also struck a balance between theoretical and application development. The conference is truly international meeting with a high level of participation from many countries. Topics covered include chemical engineering, circuits, communications systems, control theory, engineering mathematics, systems engineering, manufacture engineering, and industrial applications. The book offers the state of art of tremendous advances in engineering technologies and physical science and applications, and also serves as an excellent reference work for researchers and graduate students working with/on engineering technologies and physical science and applications.
Topics Covered Include Chemical Engineering -- Circuits -- Communications Systems -- Control Theory -- Engineering Mathematics -- Systems Engineering -- Manufacture Engineering and Industrial Applications.
Keywords: Engineering; Software engineering; Engineering mathematics; Telecommunication; Engineering; Communications Engineering, Networks; Appl.Mathematics/Computational Methods of Engineering; Software Engineering/Programming and Operating Systems; Electronic Circuits and Devices